Strengthening the Municipality's Role in Supporting Local Investment in Algeria as a Mechanism for Reforming Local Communities within the Framework of Law 10/11 - Bouaici, Azza; Belasal, Mohamed (Journal of Legal Studies and Researches, 2021)
As part of the economic reform policy adopted by the Algerian state to address the problems of the current economic and social situation, it has become heavily dependent on the adoption of the policy of local investment by relying on local communities, especially the municipality, in order to create a real alternative to the hydrocarbon economy and promote the path of development, and this vision was reflected through the passage of the municipal law 11/10.